THE IMPACT OF IT GOVERNANCE ON PROMOTING FIRM PERFORMANCE IN QATAR: A CONCEPTUAL APPROACH - Alabdullah, Tariq Tawfeeq Yousif; Churiyah, Madziatul; Ibrahim, Suraiya (Transpublika Publisher, 2023)
This study explores the impact of IT governance on enhancing firm performance in Qatar, considering its unique context as a rapidly emerging nation with a burgeoning digital landscape. IT governance, as an extension of corporate governance, plays a pivotal role in improving operational efficiency, aligning strategies, managing risks, and creating value through technology. Drawing upon existing literature and theoretical frameworks, the study introduces a model that identifies key factors such as IT strategy formulation, IT infrastructure management, IT risk management, IT investment decision-making, and IT performance measurement, elucidating how IT governance influences business success. By synthesizing these concepts, this research lays the foundation for future empirical investigations, highlighting the critical role of effective IT governance in achieving superior firm performance in Qatar and similar contexts. The findings carry practical implications for practitioners, policymakers, and researchers aiming to enhance IT governance practices and understand their impact in Qatar's evolving digital landscape, ultimately contributing to our comprehension of how IT governance shapes organizational success and competitiveness in this dynamic environment.